2010
DOI: 10.1016/j.chom.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Rac GTPase by the NLR Family Disease Resistance Protein Pit Plays a Critical Role in Rice Innate Immunity

Abstract: The nucleotide-binding domain and leucine-rich repeat-containing (NLR) family proteins recognize pathogen-derived molecules and trigger immune responses in both plants and animals. In plants, the direct or indirect recognition of specific pathogen effectors by NLRs culminates in a hypersensitive response (HR) and the production of reactive oxygen species (ROS), key components of the plant defense response. However, the molecules activated by NLRs and how they induce immune responses are largely unknown. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
226
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(250 citation statements)
references
References 62 publications
4
226
0
3
Order By: Relevance
“…Two R genes, Pi9 and Pi21, confer broad-spectrum resistance against multiple races of M. oryzae [9,10]. Rac GTPasemediated events (e.g., generation of ROS), activation of MAP kinase, and other key components, such as RAR1, SGT1, Hsp90, and WRKY45, play important roles in regulating the immune response against M. oryzae [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Endogenous SA is involved in defence against M. oryzae [25].…”
Section: Introductionmentioning
confidence: 99%
“…Two R genes, Pi9 and Pi21, confer broad-spectrum resistance against multiple races of M. oryzae [9,10]. Rac GTPasemediated events (e.g., generation of ROS), activation of MAP kinase, and other key components, such as RAR1, SGT1, Hsp90, and WRKY45, play important roles in regulating the immune response against M. oryzae [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Endogenous SA is involved in defence against M. oryzae [25].…”
Section: Introductionmentioning
confidence: 99%
“…These methods exploit the selective interaction between the Cdc42/Rac interactive binding (CRIB) domain of the Rac-effector PAK1 (PAK CRIB) and plant and animal Rac GTPases. PAK CRIB shows a high affinity only for the active GTP-bound form of Rac, and not for the inactive GDP-bound form (17,19). PAK CRIB binding suppresses the intrinsic GTPase activity of Rac, and this function provides a useful tool for isolating active GTP-bound forms of Rac/ROP from crude cell lysates and for monitoring the activation state of Rac/ROP in living cells.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…Currently, two alternative non-radioactive techniques are available for monitoring the in vivo activation of Rac/ROP: a PAK CRIB pull-down assay, and FRET sensors (5,(17)(18)(19). These methods exploit the selective interaction between the Cdc42/Rac interactive binding (CRIB) domain of the Rac-effector PAK1 (PAK CRIB) and plant and animal Rac GTPases.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…npg Together this emerging body of data support the idea that the activity of GTPases is monitored by NLR and related pathways, and used as a cue to augment ongoing immune responses during pathogen invasion. Interestingly, Kawano and colleagues have shown that resistance to the rice blast fungus also involves activation of Rac (OsRac1) downstream of Pit, a plant nucleotidebinding site-leucine-rich repeat (NBS-LRR) receptor [10]. OsRac1 contributes to NBS-LRR-mediated production of ROS and induction of a hypersensitive response for the purpose of destroying infected tissue and preventing dissemination.…”
mentioning
confidence: 99%